Design and Implementation of a Lecture Scheduling System - Haditya Prasetyo; Hafid Dwi Adha; Lova Endriani Zen; Mhd. Adhitiya Okta Riyandi; Hafizah Hanim (Jurnal Informatika Ekonomi Bisnis, 2026)
The lecture schedule is very important in the world of higher education. The lecture schedule enables lecturers and students to conduct a structured and well-planned teaching and learning process. Lecturers, students, faculty, and campuses can all benefit from a systematic lecture schedule that facilitates the lecture process. The lecture schedule's systematic approach can aid campus administration in obtaining lecture reports quickly and easily. In this study, the design and implementation of a lecture schedule system were carried out at the Faculty of Computer Science at UIN Imam Bonjol Padang. The Waterfall model is used as the research method, which begins with needs analysis and progresses to system maintenance, while UML is used to design the system. There are three actors in this system, namely administrators, lecturers, and ordinary users. The system designed for this study has been implemented and is accessible at https://jadwalin.uinib.ac.id/.